2012
DOI: 10.1111/j.1741-2358.2012.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mandibular bone mineral density in osteoporotic, osteopenic and normal elderly edentulous subjects measured by the dual‐energy X‐ray absorptiometry technique

Abstract: Comparison of mandibular bone mineral density in osteoporotic, osteopenic and normal elderly edentulous subjects measured by the dual-energy X-ray absorptiometry techniqueObjective: The aim of this study was to compare the mandibular body bone mineral density according to bone mineral density status of spine and femur measured by dual-energy X-ray absorptiometry (DXA) technique in elderly edentulous individuals. Background: One of the factors that affect the survival rate of implants is bone mineral density (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
7
1
4
Order By: Relevance
“…In an opposite direction to the findings of Buyukkaplan et al,30 this study found that the RD value of the mandibular body of the whole bony area gave a general impression of the status of the femoral neck bone density. This might help to infer the status of one of these two locations when the status of the other site is known.…”
Section: Discussioncontrasting
confidence: 92%
“…In an opposite direction to the findings of Buyukkaplan et al,30 this study found that the RD value of the mandibular body of the whole bony area gave a general impression of the status of the femoral neck bone density. This might help to infer the status of one of these two locations when the status of the other site is known.…”
Section: Discussioncontrasting
confidence: 92%
“…The relation between age and bone loss may have been influenced by the fact that women included in this study could be in menopause, when accelerated bone loss is more pronounced than in men. Such finding was observed in other studies, which suggested that early menopause could be a risk factor for bone loss 18,19 .…”
Section: Discussionsupporting
confidence: 73%
“…The body of the mandible is also the location for implant placement, so the BMD measurements were performed on the body of the mandible, not the ramus. In this study, the authors tried to compose homogenous study populations with strict inclusion criteria to eliminate confounding factors that affect bone metabolism, such as age, 7,8 osteoporosis 21 and other systemic diseases, 22 smoking, 23 alcohol consumption, and hormone intake 22 . The distinguishing features of this study are that it was primarily designed to evaluate mandibular BMD using DXA on both male and female patients who were systemically healthy and had no risk factors for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…One error source was the superimposition of the contralateral side of the mandible. It was more prominent in the dentate group because the presence of teeth complicated the DXA image from recognizing the ideal superimposition 21,22,43 . For this reason, the clinician remained beside the patient to ensure that the scanning of the mandible was correct.…”
Section: Discussionmentioning
confidence: 99%